2020
DOI: 10.1115/1.4047047
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Nanocomposites. Part 1: Mechanical Properties

Abstract: Micromachining of nanocomposites is deemed to be a complicated process due to the anisotropic, heterogeneous structure, and advanced mechanical properties of these materials associated with the size effects in micromachining. It leads to poorer machinability in terms of high cutting force, low surface quality, and high rate of tool wear. In part 1 of this two-part review paper, a comprehensive review on mechanical properties of various nanocomposites will be presented while the second part of the paper will fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 284 publications
(241 reference statements)
1
8
0
Order By: Relevance
“…Some similar findings could be found in [31,32]. The improvements of tensile strength and modulus combined with the decrease of strain failure could be used to explain the effects of filler content on the machinability of these nanocomposites (i.e., cutting force, surface roughness, chip formation) [19]. Furthermore, the thermal conductivity of these nanocomposites should also be considered since it could also influence the micromachining process in particular when thermal softening phenomenon was dominant (at high cutting speed).…”
Section: Tensile Propertiessupporting
confidence: 67%
See 2 more Smart Citations
“…Some similar findings could be found in [31,32]. The improvements of tensile strength and modulus combined with the decrease of strain failure could be used to explain the effects of filler content on the machinability of these nanocomposites (i.e., cutting force, surface roughness, chip formation) [19]. Furthermore, the thermal conductivity of these nanocomposites should also be considered since it could also influence the micromachining process in particular when thermal softening phenomenon was dominant (at high cutting speed).…”
Section: Tensile Propertiessupporting
confidence: 67%
“…It is possibly due to the higher cost of CNTs compared to CF that prevented these nano-fibres from being applied in large structures [18]. Furthermore, the literature review from [19] showed that the primary barrier that limited the applications of CNT based nanocomposites was the synthesis optimisation. Uniform CNT distribution and CNT agglomeration have been still the main problems that reduce their reinforcing effectiveness of this nano-filler in polymer nanocomposites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of nanoparticles into the polymer matrix could significantly enhance the mechanical properties. 1–11 Long et al proposed that polymer chains can form binding layers around nanoparticles, which are like carbon-reinforced rubber. 12,13 An alternative explanation proposed by Goritz and Sternstein was that polymer chains can form a “bridge” between nanoparticles, allowing the formation of a percolation network in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the interphase nature is a crucial factor that affects the performance of CNTs/epoxy composites, which is directly decided by the surface property of CNTs. [4][5][6][7][8][9][10] Liu et al 11 investigated the interphase structure between graphene (GP) and the epoxy matrix. It indicated that both interphase thickness and density of GP/epoxy composites are higher than those of GP oxide/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%